The future of history - Lukacs, John, 1924-2019. (New Haven, Conn. ; London : Yale University Press, 2011)
A reflection on the past and the future of the study of history.
Historianship -- Problems for the profession -- Appetite for history -- Re-cognition of history as literature -- History and the novel -- Future of the profession -- Tradition, inheritance, and imagination -- Apologia.
Keywords: Historiography -- History; Historiography -- Philosophy; History -- Philosophy; History -- Methodology; Historians